101 Effects of two sward heights on forage nutritive value, rumen digestion, and grazing behavior of steers grazing non-endophyte infected tall fescue pastures. (29th July 2019) - Diaz, Jose M; Philipp, Dirk; Coffey, Ken; Beck, Paul A; Hansen, Christopher; Niyigena, Valens; Rhein, Robert
Abstract: The objective of this experiment was to evaluate the effects of two different sward heights on diet composition, rumen fermentation, and behavior of steers grazing E- tall fescue pastures. Steers (n = 4; BW = 400kg) were randomly assigned for 5 d to long (LSR) or short (SSR) sward paddocks in a cross-over design with two periods. Sward heights were 12.7±1.45cm for LSR, 11.1±0.75cm for SSR period 1 and 11.6±0.60cm for LSR and 10.2±0.70cm for SSR period 2. Forage grab samples were obtained immediately prior to the start of grazing to estimate nutritive value. Animal diet selection was determined via rumen sampling following complete rumen evacuation on d 4 after animals grazed for 20 to 30 min. Rumen fluid was collected on d 3 every 2 h from 0700 to 1900h to estimate Ammonia, VFA, and pH. During d 1 and d 2 of each period, visual observations of grazing behavior were made every hour for 10 min for each animal to record grazing, idling, lying, and ruminating time. Forage nutritive value did not differ between treatments (P > 0.05). No treatment differences were observed for diet selection (P > 0.05); masticate samples following evacuation resulted in 56% NDF, 23% ADF, and 26% CP. There was no treatment×time interaction (P > 0.05) and no treatment differences (P > 0.05) for ammonia (29.9 mM/L), VFA (49.8 mM/L), or pH (6.7) based on rumen fluid sampling on d 3. No differences (P > 0.05) in grazing behavior between treatments were observed. Average time spent grazing were 8.35 min/10 min of observation between 0700 and 0900h. Bite rates did not differ (P > 0.05) between treatments (40 bites/min) during same time periods. Results suggested that variability of grazing behavior is high among animals and further research is needed to detect differences based on forage sward heights